Paroxysmal sympathetic hyperactivity and refractory hypotension in Guillain-Barré syndrome with autoimmune encephalitis: a case report and literature review - Wang, Jun-Ping; He, Yan-Bo (Frontiers in Neuroscience, 2025)
Guillain-Barré syndrome (GBS) is an acute inflammatory peripheral nerve disorder mediated by autoimmune mechanisms. However, its co-occurrence with autoimmune encephalitis (AE) is rare. We present a 51-year-old man who initially presented with symmetrical numbness and weakness in all limbs, followed by hallucinations, behavioral abnormalities, and consciousness disturbances. Cerebrospinal fluid (CSF) analysis revealed protein-cell dissociation, indicative of GBS. Brain magnetic resonance imaging (MRI) showed abnormal signals in the splenium of the corpus callosum. Electromyography showed reduced amplitude in motor nerve conduction of bilateral common peroneal nerves and left tibial nerves. He developed respiratory distress, requiring tracheal intubation and mechanical ventilation. Finally, he was diagnosed with GBS combined with AE and received treatment with intravenous immunoglobulin (IVIG) and plasma exchange (PLEX). Subsequently, he experienced paroxysmal sympathetic hyperactivity (PSH) and refractory hypotension requiring vasopressor support. After comprehensive treatment, he was successfully weaned off the ventilator, and his refractory hypotension resolved after more than six months. This case illustrates that severe autonomic dysfunction can occur at any stage of GBS companied with AE. Furthermore, these patients often require prolonged ICU stays and experience slower recovery, but may still achieve a favorable outcome with appropriate integrated therapy.